Development of Managerial Competencies of Students on the Basis of Democratization and Informatization of Educational Process at the University - I. L. Zagoumennov (Открытое образование (Москва))
The purpose of the work. The purpose of the work is to substantiate and test a practice-oriented interactive information and pedagogical technology aimed at the formation and development of managerial competencies of students and undergraduates studying in the direction of “Management". The relevance of this problem is due to the transition of the national economy to an innovative development path and the demand for specialists with both a system of professional knowledge and the ability to successfully solve practical and theoretical problems in their workplaces, including using modern information technologies.Materials and methods. To achieve this purpose, methods of analysis and comparison of already existing approaches to solving the problem were used, and the general scientific system approach was used as the main method, the basis of which is the consideration of subjects and objects of educational activity in a higher educational institution as elements of a management system. In this context, the educational activities of students are studied from the standpoint of the democratization of management, including co-management and self-governance. In order to increase the effectiveness of the educational process, the possibility of using the distance learning system (DLS) of Moodle as a software environment for the development and placement of educational and methodological materials, the organization of the educational process based on them, including the assessment of educational achievements of students, is considered. Testing of the developed technology was carried out in the Minsk branch of Plekhanov Russian University of Economics in work with students within the framework of academic disciplines of the training direction — “Management: 38.03.02”, profile of the program —“Organization Management” and “Crisis Management”, higher education level — “Bachelor”, as well as working with undergraduates training direction 38.04.02 “Management”, profile of the program “Strategic and Corporate Governance”.Results. As part of the study, an interactive information and pedagogical technology using the Moodle distance learning system (DLS) was developed and tested, based on the involvement of students in management activities, using democratization inclusive mechanisms in the educational process, and promoting the development of the team’s organizational culture and ability to work in student and master groups competitive environment. The proposed information and pedagogical technology makes it possible to give the training of students and undergraduates a practice-oriented character in their first year of study at the university. A survey of students and undergraduates during and following the study of academic disciplines using the information and pedagogical technology under consideration indicates that they welcome it. The vast majority of students and undergraduates in the questionnaires noted that they are satisfied with the quality of teaching and the results of their own activities, as well as the positive team relationships that are formed as a result of work.Conclusion. The proposed technology harmoniously combines the best that is in the “live” and “virtual” interaction of the subjects of the educational process, and allows you to organize managerial practice of students and undergraduates directly in the classroom. Thus, already at the first stages of training at the university, a practice-oriented approach is implemented, aimed at the formation and development of students and undergraduates of managerial digital competencies in demand in modern economics and society.